Motivators for Cannabis Use Among Young Adults in Outpatient Psychiatric Care: A Qualitative Study. (July 2021) - Whiteley, Laura; Haubrick, Kayla K.; Arnold, Trisha; Craker, Lacey; Olsen, Elizabeth; Hershkowitz, Dylan; Maj, Shannon; Brown, Larry K.
Cannabis use is prevalent among youth with mental illness, despite the increased risk of exacerbating psychiatric symptoms. The rapidly changing legality of cannabis has contributed to its normalization and decreased perceived risks. This study qualitatively gathered young adult psychiatric patients' ( n =15) perspectives on cannabis to inform a use reduction intervention. NVivo12 was used to organize coded data and facilitate analysis. Motivations to use included viewing cannabis utilization as normalized, supported, and a safer alternative to psychiatric medications. Facilitators for decreasing use were cannabis' inadequacy at long-term symptom relief, the negative psychiatric sequelae seen in other users, and moderation of intake. Recommendations for the intervention included avoiding overly critical content and providing behavioral skills to aid reduction while improving psychiatric symptoms. Young adults in psychiatric care have unique motivations for cannabis consumption and decreasing use, which should be targeted in future interventions.